(untitled) (jornal of the libyan geographical society, 1997)
Studies relating to the distribution of basic services in cities have recently received considerable attention from researchers and planners, perhaps due to several reasons, the most important of which are: providing information to decision-makers about the efficiency of distribution, or when considering redistribution. Or creating more of the required service units, which also reflects the desire to address the urban problems that cities face due to population growth or increased demand for basic services. The importance of this type of study in our country is underscored by the fact that the urban population now constitutes more than 75% of the total population. The city of Benghazi, the study area, is the second largest Libyan city after Tripoli, where population growth played a major role in increasing the size of the city. Since the country got rid of foreign control in 1951, until the late eighties, its population more than sextupled. This research focuses on studying basic education in the city of Benghazi within a framework based on geographical analysis, by examining the characteristics of school distribution across the city, the factors that control the selection of their locations, and the impact of this on students’ daily commutes. The analysis was based on information and data obtained from office and field sources, as a field survey was conducted of 151 schools distributed across the city’s 21 districts.